Pengembangan Sistem Pengelolaan Perizinan Ruang Laut dan Pesisir Berbasis WebGIS Dengan Penerapan OpenLayers (Studi Kasus: Dinas Kelautan dan Perikanan Provinsi Jawa Timur) - Charisma Amadea Putri; Denny Sagita Rusdianto; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The East Java Provincial Fisheries Office works in the marine and fisheries sector. One of the fields owned, namely the Marine, Coastal and Supervision sector which is responsible for managing marine and coastal space permit recommendations. The licensing has a flow starting from the process of the applicant submitting an application, processing the data by the East Java Provincial Fisheries Office, conducting a field survey and then making a report as a reference in making recommendations. The process takes quite a long time, namely when the process of sending letters to service branches and during the location verification process so that the time required is 30 days or more, while the time limit given by the government is only 15 working days. In addition, the lack of knowledge about spatial data used in regional data collection causes workers to have difficulty in carrying out regional data collection. From these problems, a solution was found by making a marine and coastal space permit processing system equipped with the ability to process spatial data in easy-to-understand stages. The system is built using the waterfall Software Development Life Cycle method. This research begins with analysis and design by making a Use Case Diagram which states that there are 55 functional needs plus 1 non-functional requirement. There are several main features, namely adding a copy of the letter, data collection of areas and adding dispositions, then making Sequence Diagrams and Class Diagrams. System development is carried out using Laravel as a framework, PHP for programming languages, MySQL for databases and OpenLayers for GIS creation. After the system has been successfully built, unit testing with whitebox testing is carried out on 3 main system functions and produces valid value test cases, blackbox testing for validation testing carried out on 55 functional requirements, each test case is valid, and compatibility testing to test compatibility which results in a value that the system can run on a variety of web browsers as needed.